Halide perovskite nanocrystals and lanthanide complex-based bi-luminescent security ink for multilevel static-dynamic anticounterfeiting - Dubey C.; Shruti; Singh S.K.; Singh A.K. (My University, 2025)
Counterfeiting is of great concern globally and requires technological research and development for high-security encryption. In this work, we have developed a bi-luminescent security ink comprising Eu(TTA)3Phen and CsPbBr3 nanocrystals which offers multilevel anti-counterfeiting strategies. Under UV excitation, the bi-luminescent security ink shows intense red emission, whereas it emits green emission under blue light excitation. As the red transition of Eu3+ ions show a lifetime of the order of microseconds and the green band of CsPbBr3 nanocrystals of the order of nanoseconds, the ink can also be used for dynamic anticounterfeiting under a single excitation wavelength. We have successfully demonstrated the multi-stimuli anticounterfeiting application of the developed bi-luminescent security ink. The dynamic anticounterfeiting aspect has been demonstrated by making use of the phosphorescence spectrum of the printed patterns. Our results show that the developed bi-luminescent security ink is very stable under UV light, different chemical environments, and ambient environments. © 2022 Elsevier Ltd